BORROWING SYSTEM AND RETURN LIBRARY BOOK IN STATE 4 MADRASAH ALIYAH - Yeni Setiyawati; Don Elsyafitra, Skom (Jurnal Sistem Informasi, 2002)
These authors discuss the system of loaning and book return services at the library aredepicted with Files Of Document, Data Flow Diagram, Entity Relationship Diagramsand Normalization, which then created a computer application program to processloaning and book return data, which formed as a data member, data books , databooks borrowed and returned data by using Visual Basic 6.0 programming languagethat is better than the manual way.Data processing using a computer system at the rental data and return data areintended to determine the number of members, number of books borrowed and thenumber of books returned.